Development of a Next-Generation Sequencing (NGS) Gene Panel for Lysosomal Storage Diseases - Coutinho, Maria Francisca (2018)
Molecular genetic testing has not been used extensively as the primary diagnostic test for LSDs but this may change with the advent of rapid, reliable and affordable high-throughput DNA sequencing, the so called next generation sequencing. The aim of this work was to develop a next-generation sequencing (NGS)-based workflow for the identification of variations in exons and their intronic flanking regions in genes involved in lysosomal function.